2020
DOI: 10.2147/oajc.s257385
|View full text |Cite
|
Sign up to set email alerts
|

<p>Quality of Long-acting Reversible Contraception Provision in Lomé, Togo</p>

Abstract: Context: Provision of high-quality contraceptive counseling and services is essential to ensure family planning (FP) programs are rights-based and voluntary. Togo's modern contraceptive use has steadily increased with almost a quarter of the method mix attributed to longacting reversible contraceptives (LARC). The purpose of this study is to assess the quality of LARC provision in Togo. Methods: Data for this study were collected in 2016 as part of a larger research study conducted in Lomé, Togo to assess the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…For example, one study found that youth post-abortion care clients were more likely to choose a contraceptive method if the provider was trained in offering youth-friendly post-abortion care ( 5 ). A lack of basic items at the facility such as trained staff, equipment and commodities were also associated with low contraceptive uptake ( 6 ) while having health workers benefit from a supervisory visit at health facilities was associated with client uptake of long-acting reversible contraceptives in Togo ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, one study found that youth post-abortion care clients were more likely to choose a contraceptive method if the provider was trained in offering youth-friendly post-abortion care ( 5 ). A lack of basic items at the facility such as trained staff, equipment and commodities were also associated with low contraceptive uptake ( 6 ) while having health workers benefit from a supervisory visit at health facilities was associated with client uptake of long-acting reversible contraceptives in Togo ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Another increasingly used measure of quality provider-client communication is the validated three item method information index (MII) or the four item MIIplus, which assess the extent to which information about FP methods is communicated to clients [7,8]. The MII and MIIplus have been found to be positively associated with better FP continuation in Pakistan and India and the MII has also been found to be positively associated with voluntary use of long-acting reversible contraception (LARC) [7,[9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Despite its wide adoption by researchers and policy makers to evaluate the success of family planning programs, including FP2020 [23] , some scholars have questioned the validity of the measure, noting that it may overestimate the information exchanged between patients and providers during counseling [24] . Additionally, while the MII was designed to measure information given to clients during counseling, it has been routinely adopted as a proxy for the full spectrum of informed choice or for the construct of quality of care writ large [25] , [26] , [27] , [28] . This may be problematic given that the MII does not include items to capture information on correct method use, warning signs, or the range of methods presented to the client, among other elements important to informed decision-making.…”
Section: Introductionmentioning
confidence: 99%